Using human resource data to track innovation summary of a workshop - Merrill, Stephen A.; McGreary, Michael. (Compass series (Washington, D.C.), 2002)
"This volume is the summary of a second STEP workshop, chaired by board memder Mark Myers, formerly chief technical officer of Xerox Corporation. The workshop explored how data on scientists, engineers, and other professionals-data on their training and skills, mobility and career paths, use of time, relationships across institutions and sectors, and productivity-can be used to illuminate aspects of innovation that current R&D, patent and other data, by themselves, do not fully capture." -- p. viii, Preface.